A systemic approach of communication in multiple stakeholder settings: challenges and future research directions from a multidisciplinary perspective - Lievens, Annouk; Moons, Ingrid (International journal of advertising, 2023)
In this article we adopt a systemic view to investigate the multidisciplinary challenges for managing communication within complex multistakeholder settings. We zoom in on communication challenges from a multilevel perspective distinguishing a macro level (i.e. the entire stakeholder network), a meso level (i.e. communication and media players connecting the macro - and micro level) and a micro level (i.e. stakeholder engagement journey). In doing so, we review literature from multiple research domains within and across marketing communication and (social) sciences disciplines, we derive the main research gaps and propose a more diversified and multidisciplinary approach in addressing future communication research in complex multistakeholder settings.